Selectivity in posting on social networks: the role of privacy concerns, social capital, and technical literacy. Issue 2 (February 2020) - Schwartz-Chassidim, Hadas; Ayalon, Oshrat; Mendel, Tamir; Hirschprung, Ron; Toch, Eran
Abstract: People's posting behaviors in social networks was perceived as ambiguous, with concerns misaligned with people's public postings. To address this gap, we suggest a model that offers new insights into the relationship between perceptions and actual behaviors. We define a quantitative marker for agility, the frequency in which people update their audience selection when posting information in online social networks, and evaluate the factors that contribute to the variability of agility between different users. We analyzed the posting behavior of Facebook 181 participants, as well as their answers to open and close questions. We find that frequent changes in privacy settings are correlated with high social privacy and with institutional privacy concerns, whereas social concerns were found to be more prominent. Agility was negatively correlated with low public sharing. Our findings show that users use privacy settings to effectively mitigate privacy concerns and desires for creating and strengthening social connections. We discuss how agility can be used to design and to evaluate new user interfaces for managing privacy in social settings. Abstract : Privacy, Online social networks, Privacy controls, Social capital, Behavior analysis, Boundary regulation theory, Facebook, Computer privacy; Cognitive aspect of human-computer system; Interaction design; User interface; Software engineering, Computer science, Psychology